Розвідки у верхів’ях Західного Бугу у 2009 р. - Сало, Б.Я. (Археологічні дослідження в Україні, 2010)
The main goal of the archaeological prospecting in the upper reaches of the Western Buh River was the search for monuments and their localization on the archaeological map of Lviv Oblast.